2022
DOI: 10.1080/13880209.2022.2102657
|View full text |Cite
|
Sign up to set email alerts
|

Aaptamine – a dual acetyl – and butyrylcholinesterase inhibitor as potential anti-Alzheimer’s disease agent

Abstract: Context Alzheimer’s disease (AD) is a neurodegenerative disorder that affects millions of people worldwide. Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) are promising therapeutic targets for AD. Objective To evaluate the inhibitory effects of aaptamine on two cholinesterases and investigate the in vivo therapeutic effect on AD in a zebrafish model. Materials and methods Aaptamine was isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…468 Promiscuous alkaloid aaptamine is a dual inhibitor of both acetyl- and butyryl-cholinesterase and therefore has potential as an Alzheimer's disease therapeutic lead. 469 HTS of 300 marine invertebrate extracts from Australia has revealed that the known guanidine-based, plant growth promoter asterubine binds to α-synuclein, therefore making it a lead for Parkinson's disease; asterubine structurally resembles the β-amyloid aggregation inhibitors drugs tramiprosate and ALZ-801. 470 The same HTS campaign also identified (+)-aerothionin-1 and -2 as α-synuclein inhibitors; interestingly both inhibit protein aggregation but while (+)-aerothionin-1 is toxic to dopaminergic neuronal cells, −2 is not.…”
Section: Spongesmentioning
confidence: 99%
“…468 Promiscuous alkaloid aaptamine is a dual inhibitor of both acetyl- and butyryl-cholinesterase and therefore has potential as an Alzheimer's disease therapeutic lead. 469 HTS of 300 marine invertebrate extracts from Australia has revealed that the known guanidine-based, plant growth promoter asterubine binds to α-synuclein, therefore making it a lead for Parkinson's disease; asterubine structurally resembles the β-amyloid aggregation inhibitors drugs tramiprosate and ALZ-801. 470 The same HTS campaign also identified (+)-aerothionin-1 and -2 as α-synuclein inhibitors; interestingly both inhibit protein aggregation but while (+)-aerothionin-1 is toxic to dopaminergic neuronal cells, −2 is not.…”
Section: Spongesmentioning
confidence: 99%
“…MAOs are membrane bounded and flavin adenine dinucleotide (FAD) dependent enzymes associated with outer membrane of mitochondria found in glial [14] and neuronal cells, [15] which belong to proteaceous family containing flavin amine oxidases. These are responsible for the degradation of chemical messengers (neurotransmitters) like dopamine, 5‐HT (serotonin), adrenalin, noradrenalin and deamination of phenylisopropylamine [6,16] . These are also present in different cells but more prominently in brain and liver cells [17] .…”
Section: Introductionmentioning
confidence: 99%
“…[5] Serine hydrolases containing two important enzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) are generally known as cholinesterases (ChEs). [6] Both enzymes are different in their substrate selectivity. [7] Acetylcholinesterase hydrolyzes the acetylcholine into choline and acetate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aaptamines are a class of alkaloids derived from marine sponges, particularly from Aaptos sp., with cytotoxic, antifungal, and antibacterial activities [ 1 , 2 , 3 ]. Recent studies disclosed the potential of aaptamine as therapeutic agent for neuropathic pain or Alzheimer’s disease [ 4 , 5 ], enhancing the importance of the compound. Demethyl(oxy)aaptamine ( 1 in Figure 1 ) [ 6 ], an oxidized aaptamine derivative, is also known for its interesting biological activities.…”
Section: Introductionmentioning
confidence: 99%